A newly discovered novel and its transnational author: Maria Severn by Francisca Wood - Pazos Alonso, C (Modern Humanities Research Association, 2016)
This article focuses on a transnational Portuguese woman of letters, Francisca Wood, and her novel Maria Severn (1869), initially serialized in the pioneering weekly periodical that she directed, A Voz Feminina, later renamed O Progresso (1868–69). It draws on preliminary archival research to provide new biographical information on Wood, which sheds fresh light on her progressive convictions and British connections. Using as source text what appears to be the only surviving copy of Maria Severn in book form — recently discovered in the British Library — I examine the role of Wood as cultural mediator and suggest that the incontrovertible originality of her novel may stem from her creative assimilation of Jane Austen, Elizabeth Gaskell and George Eliot.